Creating Resilient Supply Chains: A Practical Guide - (:unkn) unknown (Cranfield University School of Management, 2003)
The events of the last few years from the fuel crisis to foot and mouth disease to SARS, have highlighted the vulnerability of many supply chains. Quite apart from the external challenges to supply chain continuity are those possible sources of risk that are internal to the supply chain. A number of concurrent trends have contributed to the fragility that some observers believe now characterises many supply chains. These trends include the rapid growth in global sourcing and offshore manufacturing; the continued move to reduce the supplier base; industry consolidation and the centralisation of distribution facilities to name just a few. Following from the earlier report prepared for the DETR in 2002, Supply Chain Vulnerability, this report builds upon that work to identify the opportunities for the creation of more resilient supply chains. As the research progressed, it became clear that there is still a lack of understanding of where an individual organisation might sit in the wider supply network. Few companies seemed to have real visibility beyond their first tier suppliers or downstream beyond their immediate customers. This work, undertaken by the Cranfield Centre for Logistics and Supply Chain Management at Cranfield University and funded by the Department for Transport, is empirically based and draws on insights from a number of ‘critical’ industrial sectors including food retailing, oil and petrochemicals, pharmaceuticals, packaging, electronics, transport services and the distribution of automotive spares. It also includes input from private and public sector organisations involved in the provision of health care and in defence. In particular it focuses on the development of a managerial agenda for the identification and management of supply chain risk, with recommendations to improve the resilience of supply chains. During the research we were concerned that the outputs, including this Executive Report, would address the needs of small and medium enterprises (SMEs) and provide relevant and practical tools to assist them to manage their supply chain risks.